Pengaruh Temperatur terhadap Kekuatan Impak pada Material Besi Nako 10 mm - Saragi J F HT; Pratama A B; Boangmanalu E P D; Al Qadry; Sinaga F T H (Cered Indonesia Institute, 2023)
Each material has a different type of toughness, such as the type of 10 mm nako iron material. In use, the material can be damaged. One of the factors that can cause damage is temperature. To find out how the effect of temperature on the material, one of the material tests was carried out, namely impact testing with the charpy method. This impact test is carried out on materials that have been given different temperature variations. There are 6 test specimens used at different temperatures. As a result, at the highest temperature, namely at 31 oC, the absorbed energy is 180.84 J with an impact price of 180.84 J/cm2 and at a low temperature, namely at 4 oC, the absorbed energy is 256.8 J with an impact price of 256 .8 J/cm2.